FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PROGRAM PEMBERIAN KAPSUL VITAMIN A PADA IBU NIFAS OLEH BIDAN DESA DI WILAYAH DINAS KESEHATAN KABUPATEN SLEMAN - Susilowati, Apriliana; Sriatmi, Ayun; Arso, Septo Pawelas (Jurnal Kesehatan Masyarakat (Undip), 2015)
One of the objectives the policy implementation function is to identify accurately the actual factors that influence the success or failure the implementation a program of health policy. The presence indicator of vitamin A coverage performance figures for post partum mothers by midwives in the area of Sleman District Health Office has increased significantly from 2009 to 2012. It was necessary to investigate the factors that influence the successful implementation of vitamin A supplementation program for puerperal women by midwives in the Sleman District Health Office by using a model approach to the implementation of public policy theory Van Meter and Van Horn. The method used quantitative method with cross sectional approach. Samples 47 midwives who met the inclusion criteria. Data collection tool was a questionnaire. From the research that the factors studied were working guidelines, resources, supervision , communication, attitude of the implementers and support environment Percentage of start is greatest successive environmental factors support midwives as executor implementation of programs ( 74.5 % ) very influential in supporting the implementation of the program, a factor goes supervision of stakeholders ( 63.8 % ) midwives feel less supervision goes well , a factor working guidelines of the program ( 61.7 % ), communication between program managers ( 61.7 % ), the attitude factor implementing the program ( 53.2 % ), and the factor of resources of the program ( 51.1 % ), implementation of vitamin A supplementation programs for post-partum mothers by midwives in the area of Sleman District Health Office is generally viewed from the six factors are still below the standard that is equal to 53.2 %. Respondents who consider the passage of program implementation of vitamin A supplementation for postpartum mothers are already well.